Abnormal P-selectin localization during megakaryocyte development determines thrombosis in the gata1low model of myelofibrosis. (November 2014) - Zetterberg, Eva; Verrucci, Maria; Martelli, Fabrizio; Zingariello, Maria; Sancillo, Laura; D'Amore, Emanuela; Rana, Rosa Alba; Migliaccio, Anna Rita
Abstract Patients with primary myelofibrosis have increased risk for bleeding and thrombosis. It is debated whether propensity to thrombosis is due to increased numbers of platelet microparticles and/or to pathological platelet-neutrophil interactions. Platelet neutrophil interactions are mediated by P-selectin and even though the megakaryocytes of myelofibrosis patients express normal levels of P-selectin, it remains abnormally localized to the demarcation membrane system rather than being assembled into the α-granules in platelets. Mice carrying the hypomorphic Gata1low mutation express the same megakaryocyte abnormalities presented by primary myelofibrosis patients, including abnormal P-selectin localization to the DMS and develop with age myelofibrosis, a disease that closely resembles human primary myelofibrosis. Whether these mice would also develop thrombosis has not been investigated as yet. The aim of this study was to determine whether Gata1low mice would develop thrombosis with age and, in this case, the role played by P-selectin in the development of the trait. To this aim, Gata1low mice were crossed with P-selnull mice according to standard genetic protocols and Gata1lowP-selwt, Gata1lowP-selnull and Gata1WTP-selnull or Gata1wtP-selwt (as controls) littermates obtained. It was shown that platelet counts, but not hematocrit, are reduced in Gata1low mice. Moreover, platelet microparticles are reduced in Gata1low mice and P-selectin positive platelet microparticles were not found. To determine the phenotypic implications of the different mutations, bleeding time was estimated by a tail cut procedure. Mutant mice were sacrificed and presence of thrombosis was determined by immunohistological staining of organs. Gata1low mice with or without the P-selectin null trait had a prolonged bleeding time compared to wild type mice. However, in Gata1low mice significantly higher frequency of thrombotic events was seen in adult and old Gata1low mice compared to Gata1lowP-selnull mice. Thus, presence of the P-selectin null trait rescued Gata1low mice from the thrombotic phenotype, but did not change the level of platelet microparticles. Taken together these data indicate that abnormal localization of P-selectin, induced by the Gata1low mutation, and thus, increased pathological interactions with leucocytes, is responsible for the increased presence of thrombosis seen in these mice.